2019
DOI: 10.1002/nme.6241
|View full text |Cite
|
Sign up to set email alerts
|

An artificial compressibility ensemble algorithm for a stochastic Stokes‐Darcy model with random hydraulic conductivity and interface conditions

Abstract: We propose and analyze an efficient ensemble algorithm with artificial compressibility for fast decoupled computation of multiple realizations of the stochastic Stokes-Darcy model with random hydraulic conductivity (including the one in the interface conditions), source terms, and initial conditions. The solutions are found by solving three smaller decoupled subproblems with two common time-independent coefficient matrices for all realizations, which significantly improves the efficiency for both assembling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…In order to decouple the velocity and pressure in the Navier-Stokes equations, we follow the idea of artificial compressibility method [17,19,39,68,75] and replace the divergence-free condition by…”
Section: An Unconditionally Stable Coupled Time-stepping Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to decouple the velocity and pressure in the Navier-Stokes equations, we follow the idea of artificial compressibility method [17,19,39,68,75] and replace the divergence-free condition by…”
Section: An Unconditionally Stable Coupled Time-stepping Methodsmentioning
confidence: 99%
“…Furthermore, it is desirable to separate the computation of velocity and pressure when solving the Navier-Stokes equations. Due to the presence of the nonlinear Lions domain interface boundary condition, we adopt a special method of artificial compressibility [19,39] which avoids boundary conditions in the update of the pressure. We rigorously establish the unconditional long-time stability of the proposed algorithm and verify numerically that the fully discrete schemes are convergent and energy-law preserving.…”
Section: Introductionmentioning
confidence: 99%
“…In [9], the authors proved the BJ interface condition is more accurate compared with BJS interface condition from a mathematical point of view. There has been a great deal of achievements for solving such system [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The Robin-Robin domain decomposition methods, as a sense of continuous decoupling method, provides a natural and efficient means for multi-domain and multi-physics coupled problems.…”
Section: Introductionmentioning
confidence: 99%
“…The authors used the dual-porosity equations over Darcy's region to describe fluid flowing through the multiple porous medium. Recently, several related research on the above model can be found in the literatures [2,3,24,29,44]. In particular, Gao and Li [24] proposed a decoupled stabilized finite element method to solve the coupled dual-porosity-Navier-Stokes fluid flow model in the numerical field.…”
Section: Introductionmentioning
confidence: 99%